Teaching social behaviour to individuals diagnosed with autism spectrum disorder using the cool versus not cool procedure in a small group instructional format. Issue 2 (2nd April 2016) - Au, Angel; Mountjoy, Toby; Leaf, Justin B.; Leaf, Ronald; Taubman, Mitchell; McEachin, John; Tsuji, Kathleen
ABSTRACT: Background Children with autism spectrum disorder have impairments in social behaviours that require systematic intervention. The purpose of this study was to evaluate the cool versus not cool procedure implemented in a small group (dyad). Method The cool versus not cool procedure consisted of the researcher demonstrating the targeted behaviour both correctly and incorrectly and having the participants discriminate the demonstration. If the participants were unable to reach mastery, additional components were added. The researchers utilised a multiple-probe design to evaluate the cool versus not cool procedure. Results Results indicated that participants were able to reach mastery criterion on some of the social skills with the demonstration alone whereas some skills required either role-playing or feedback during probes. Conclusions The results showed that the cool versus not cool procedure was somewhat effective in increasing social behaviours; however, some skills required additional components for participants to reach mastery criterion.